Matter over mind? How the acceptance of digital entities depends on their appearance, mental prowess, and the interaction between both. Issue 142 (October 2020) - Stein, Jan-Philipp; Appel, Markus; Jost, Alexandra; Ohler, Peter
Highlights: Human-like digital agents may evoke aversion due to their embodiment and mind. Both factors are usually studied separately, neglecting interaction effects. We present an experiment exploring the interplay of artificial bodies and minds. A human-like embodiment increases people's aversion to simple-minded agents. Artificial intelligence is always seen as eerie, regardless of its body. Abstract: Digital technologies are advancing rapidly, growing to be more human-like and intelligent by the day. However, research shows that a machine's resemblance to humans can reach a critical level, which makes it seem uncanny to observers. While scholars have discussed this effect in terms of both human-like appearances and mental abilities, a potential interaction between the two aspects has hardly been addressed in literature. We designed a two-factorial experiment to overcome the identified research gap, introducing participants to digital agents with varying embodiment (text interface/human rendering) and mental capacity (simple algorithms/complex artificial intelligence). Our results show that the interaction of both factors indeed affects participants' experience in a crucial way: Whereas an agent based on simple algorithms only evokes discomfort when embedded in a human-like body, the artificial intelligence is always perceived as eerie, regardless of its embodiment. Yet, additional findings raise doubts on the unidimensionality of participants' affective response.